Single-locus species delimitation: a test of the mixed Yule–coalescent model, withan empirical application to Philippine round-leaf bats - Esselstyn, Jacob A.; Evans, Ben J.; Sedlock, Jodi L.; Anwarali, F. A.; Heaney, Lawrence R. (The Royal Society, 2012)
Prospects for a comprehensive inventory of global biodiversity would be greatly improved by automating methods of species delimitation. The general mixed Yule–coalescent (GMYC) was recently proposed as a potential means of increasing the rate of biodiversity exploration. We tested this method with simulated data and applied it to a group of poorly known bats (Hipposideros) from the Philippines. We then used echolocation call characteristics to evaluate the plausibility of species boundaries suggested by GMYC. In our simulations, GMYC performed relatively well (errors in estimated species diversity less than 25%) when the product of the haploid effective population size (Ne) and speciation rate (SR; per lineage per million years) was less than or equal to 105 , while interspecific variation in Ne was twofold or less. However, at higher but also biologically relevant values of Ne SR and when Ne varied tenfold among species, performance was very poor. GMYC analyses of mitochondrial DNA sequences from Philippine Hipposideros suggest actual diversity may be approximately twice the current estimate, and available echolocation call data are mostly consistent with GMYC delimitations. In conclusion, we consider the GMYC model useful under some conditions, but additional information on Ne, SR and/or corroboration from independent character data are needed to allow meaningful interpretation of results.